2007
DOI: 10.1002/app.25482
|View full text |Cite
|
Sign up to set email alerts
|

The effect of citrate esters as plasticizers on the thermal and mechanical properties of poly(methyl methacrylate)

Abstract: Plasticizers play a key role in the formulation of polymers and in determining their physical properties and processability. This study examines the effects of citrate esters, triethylcitrate, and triacetine as plasticizers on the thermal and mechanical properties of poly(methyl methacrylate). The samples were characterized by differential scanning calorimetry, dynamical mechanical analysis, and mechanical testing under different plasticizer contents. Both citrate esters proved to be effective as plasticizers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…This point, dividing antiplasticization and plasticization behavior, is typical for each polymerplasticizer system [42]. Gutierrez-Villarreal [38] reported an antiplasticization effect for PMMA plasticized with TEC at low concentration of plasticizer (about 13 wt%). The plasticization threshold for TEC plasticized samples based on CAB was not observed in the range of concentrations used in this study.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…This point, dividing antiplasticization and plasticization behavior, is typical for each polymerplasticizer system [42]. Gutierrez-Villarreal [38] reported an antiplasticization effect for PMMA plasticized with TEC at low concentration of plasticizer (about 13 wt%). The plasticization threshold for TEC plasticized samples based on CAB was not observed in the range of concentrations used in this study.…”
Section: Resultsmentioning
confidence: 77%
“…To the contrary, samples plasticized with TEC showed a common trend: with increasing plasticizer content, the tensile strength decreased, while elongation at break increased. Antiplasticizing effects were previously observed by Donempudi et al for PVC membranes plasticized with phthalates [37], reported for citrate esters used as plasticizers for poly(methyl methacrylate) (PMMA) [38], and also has been found for polycarbonate, polysulfone, polystyrene plasticized with various plasticizers [39]. Even though the phenomenon of antiplasticization has been already long observed in synthetic polymers, the mechanisms involved are not perfectly known.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, good miscibility between PLA and plasticizers is essential. Various plasticizers, which have been proved as effective plasticizers for PLA, citrate esters are used as plasticizers with a variety of different polymers such as poly (methyl methacrylate) [18] and cellulose acetate [19] . They are nontoxic and approved for use as additives in food, personal care products, and in medical plastics [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Various plasticizers, which have been proved as effective plasticizers for PLA, citrate esters are used as plasticizers with a variety of different polymers such as poly (methyl methacrylate) [18] and cellulose acetate [19] . They are nontoxic and approved for use as additives in food, personal care products, and in medical plastics [18] . The reason for good solubility of citrate plasticizers in PLA is due to the polar interactions between the ester groups of PLA and the plasticizer [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Fox equation is often applied to predict the glass temperature of random copolymers (Tang et al, 2010;Liu and Urban, 2009;Wei et al, 2009) and plasticized polymers (Gutierrez-Villarreal and Rodríguez-Velazquez, 2007;Blasi et al, 2007;Pillin et al, 2006) based on compositions of two components. This semi-empirical equation, as well as Gordon Taylor equation (Gordon and Taylor, 1952), has been applied to drug-polymer systems to study the miscibility of the binary components (Qian et al, 2010a;Haddadin et al, 2009;Tong and Zografi, 2001;Matsumoto and Zografi, 1999).…”
Section: Determination Of Drug Solubility At Elevated Temperatures Usmentioning
confidence: 99%